Electrochemical Determination of Uric Acid Using a Nanocomposite Electrode with Molybdenum Disulfide/Multiwalled Carbon Nanotubes (Mos2@Mwcnt) - Segura-Segura, R; Segura-Segura, R; Paz de la Vega-Quiroz, A; Paz de la Vega-Quiroz, A; Liendo-Ibarra, F; Liendo-Ibarra, F; Penagos-Llanos, J; Penagos-Llanos, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This paper presents an application for a molybdenum disulfide nanomaterial with multiwalled carbon nanotubes (MoS2@MWCNT/E) in a modified electrode substrate for the detection of uric acid (UA). The modified electrode generates a substantial three-fold increase in the anodic peak current for UA compared to the unmodified MWCNT electrode (MWCNT/E). The MoS2@MWCNT/E surface was characterized by cyclic voltammetry (CV), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and electrochemical impedance spectroscopy (EIS). The achieved detection limit stood at 0.04 µmol/L, with a relative standard deviation (RSD) of 2.0% (n = 10). The method’s accuracy, assessed through relative error and percent recovery, was validated using a urine standard solution spiked with known quantities of UA. © 2024 by the authors.
Keywords: molybdenum disulfide; multiwalled carbon nanotubes; uric acid; modified electrodes